Influence of recycled glass on the mechanical properties of self-compacting concrete and the capacity of use in Ayacucho city (Gaceta Técnica, 2024)
Concrete is the most widely used component in the construction sector, however, its exposure to the environment usually influences its behavior, which is why experts continually investigate to ensure that it meets or satisfies the specifications for which it was made. Therefore, the main objective of this work was to determine how recycled glass contributes to the mechanical properties of self-compacting concrete and its capacity for use in the city of Ayacucho, Peru. Experimentation was carried out with a standard sample and others were 7,5%, 15%, 22,5% and 30% of fine aggregate was partially replaced by recycled glass. From this study, the results obtained showed that the incorporation of glass increased the compressive strength by 13,01%, the tensile strength by 17,75%, the flexural strength improved by 27,87% and the resistance The durability to magnesium sulfate, which must be less than 15%, complies with the 3 additions, the concrete with the replacement of 30% AF by VR does not comply with the parameter. Finally, mention that, with respect to the pattern concrete, the possibility of its usability being greater is increased due to the significant improvements and its resistance to weathering due to durability
Keywords: fine aggregate; recycled glass; concrete blocks; coarse aggregate